Komposter Bertenaga Surya untuk Pembuatan Pupuk Organik dan Pemberdayaan Masyarakat Desa Wanagiri - Titin Fatimah; Budiyanto, Utomo; Amalia, Anissa; Prabowo, Yani; ARIESTA, Atik; Ariyani, Pipin Farida (Ikatan Ahli Informatika Indonesia, 2025)
This community service activity aims to increase the use of solar-powered composter technology in making organic fertilizer as part of community empowerment efforts in Wanagiri Village, Saketi District, Pandeglang Regency, Banten. This technology allows the organic waste processing process to take place more efficiently by utilizing solar energy as the main resource, thereby reducing dependence on conventional energy sources and increasing environmental sustainability. The methods used in this activity include outreach regarding the importance of recycling organic waste, application of solar-powered composter technology on a household scale, technical training for the community regarding the operation and maintenance of solar-powered composters, as well as an evaluation program to ensure its sustainability. Assistance is carried out intensively to increase people's understanding and skills in using this technology independently. The results of the activity show that the use of a solar-powered composter is not only able to speed up the process of making organic fertilizer but also provides economic benefits for the people of Wanagiri Village. In addition, this community service program contributes to reducing the volume of household waste, increasing environmental awareness, and strengthening the local resource-based economy. The conclusion of this program is that the use of solar-powered composter technology has proven to be effective and can be an innovative solution in helping the Wanagiri Village community manage organic waste sustainably and improve the welfare of the village community.